Navigating academic momentum: investigating the policies, practices, and perceptions pertaining to a dual enrollment program that is accredited by the National Alliance of Concurrent Enrollment Partnerships - Gayle, Michael (My University, 2025)
This qualitative case study examines the policies, practices, and stakeholder perceptions of a dual enrollment program at a two-year community college accredited by the National Alliance of Concurrent Enrollment Partnerships (NACEP). Using Adelman’s (2006) model of academic momentum as the theoretical framework and the NACEP standards as a conceptual guide, the study explores how such accreditation influences program design, implementation, and student outcomes. The research focuses on one Midwestern institution, analyzing document artifacts and conducting interviews with eight stakeholders including faculty, counselors, and administrators. Findings reveal that NACEP accreditation provides structural clarity and academic rigor, while stakeholder collaboration enhances student access, retention, and success. Key themes include governance, curriculum alignment, faculty credentialing, evaluation strategies, and equitable outreach. The study concludes that an intentionally structured dual enrollment program can foster academic momentum by enabling students to earn transferable credits, adapt to postsecondary environments, and graduate on accelerated timelines. Recommendations highlight the need for dedicated advising, improved enrollment systems, and broader access strategies to expand program efficacy.
Keywords: Dual enrollment; National Alliance of Concurrent Enrollment Partnerships; Community college; Concurrent enrollment; Academic momentum; Perceptions